Countering Urban Redundancy with a Multipronged Strategy: Lessons from Ashram Road, Ahmedabad - Acharya, Mohik (Journal of Contemporary Urban Affairs, 2024)
Urban redundancy, often observed in the core areas of cities, poses significant challenges to sustainable development and urban vitality. This study addresses urban redundancy by proposing a quantitative framework to both identify and mitigate its effects, using Ashram Road in Ahmedabad, India, as a case study. The research employs a Multi-Criteria Decision-Making Analysis (MCDMA) based on data collected through physical surveys and literature reviews. This analysis integrates approaches such as redevelopment, adaptive reuse, policy interventions, and economic strategies to counter redundancy effectively. The findings highlight that Ashram Road's core area, despite its historical and cultural significance, faces challenges like poor maintenance, high vacancy rates, and inadequate utilization of the available floor space index (FSI). The proposed framework aims to develop context-sensitive strategies that uphold the intrinsic value of core urban areas while promoting sustainable regeneration. The study demonstrates the need for a balanced approach that combines modern development with preservation, providing insights for urban policy-making that enhances the resilience and longevity of city cores.